Men with horse drawn sleds at Dyea Canyon, ca. 1898 - Curtis, Asahel, 1874-1941 (1898)
Photographs taken by Asahel Curtis during his trip to the Klondike in 1897-1899. Caption on image: Curtis 317 Handwritten on verso: Dyea Canyon. Another source: White Pass Trail out of Skagway. PH Coll 519.317 To order a reproduction, inquire about permissions, or for information about prices see: http://www.lib.washington.edu/specialcollections/services/reproduction/reproduction Please cite the Order Number